2020
DOI: 10.1097/adt.0000000000000222
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Probability Among Tramadol Addicts

Abstract: Objectives:Tramadol addiction is one of the major addiction problems in growing countries, especially in Egypt. Moreover, there is a strong relation between suicidality and addiction even after exclusion of personality disorders; the burden of suicide adds to the burden of substance abuse in those individuals and their families. Materials and Methods:A cross-sectional descriptive study was conducted on 72 tramadol-dependent patients who were recruited randomly in this study from the addiction outpatient clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(20 reference statements)
1
1
0
Order By: Relevance
“…In line with our result, Artenie et al (2014) revealed that the main risk factor for suicide attempt among addict was increase duration of substance use [27]. Another study confirmed our result, revealed that the duration of tramadol use could be considered a strong risk factor for suicide, as increasing the duration of tramadol results in increasing suicide risk [28]. The effects of comorbid psychiatric disorders including major depression disorder, generalized anxiety disorder…”
Section: Discussionsupporting
confidence: 87%
“…In line with our result, Artenie et al (2014) revealed that the main risk factor for suicide attempt among addict was increase duration of substance use [27]. Another study confirmed our result, revealed that the duration of tramadol use could be considered a strong risk factor for suicide, as increasing the duration of tramadol results in increasing suicide risk [28]. The effects of comorbid psychiatric disorders including major depression disorder, generalized anxiety disorder…”
Section: Discussionsupporting
confidence: 87%
“…The length of time pregabalin was abused for, the highest amount taken, and the amount used daily were all positively correlated with the Beck Suicidal Ideation score. Suicidal ideation was also positively correlated with both the dose and duration of tramadol misuse, suggesting a causal relationship between the two (30) .…”
Section: Medical and Psychiatric Comorbiditiesmentioning
confidence: 91%